Optimalisasi Efisiensi Operasional Melalui Inovasi Proses di Industri Daur Ulang Plastik UMKM - Rahmi; Mahdi; Yana, Syaifuddin; Surya, Jen; Nurhadi, Alfian (Jurnal Serambi Engineering, 2025)
This article examines the role of process innovation in improving operational efficiency within the plastic recycling industry, particularly among small and medium enterprises (SMEs). Operational efficiency serves as a key factor in ensuring both sustainability and profitability amid growing environmental concerns and the global shift toward a circular economy. Through an extensive literature review of international sources, this study highlights how the adoption of technologies such as sensor-based automatic sorting systems, energy-efficient washing, the Internet of Things (IoT), and supply chain digitalization can reduce production costs, enhance product quality, and increase production capacity. However, findings also indicate that several challenges persist, including limited investment capital, low technological literacy, infrastructural disparities, and regulatory uncertainty. Therefore, the success of process innovation in the recycling industry depends heavily on collaborative support from governments, research institutions, industry associations, and NGOs. This paper contributes both theoretically and practically by proposing a conceptual framework that links process innovation, operational efficiency, and sustainability, serving as a foundation for strengthening SMEs toward an inclusive and competitive green industry